2014
DOI: 10.1155/2014/878397
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Neural Stem Cell Proliferation by Inhibition of Phosphodiesterase 5

Abstract: The involvement of nitric oxide (NO) and cyclic GMP (cGMP) in neurogenesis has been progressively unmasked over the last decade. Phosphodiesterase 5 (PDE5) specifically degrades cGMP and is highly abundant in the mammalian brain. Inhibition of cGMP hydrolysis by blocking PDE5 is a possible strategy to enhance the first step of neurogenesis, proliferation of neural stem cells (NSC). In this work, we have studied the effect on cell proliferation of 3 inhibitors with different selectivity and potency for PDE5, T0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Several studies have also reported the proneurogenic effect of sildenafil on SVZ-derived cell culture [33] and in animal models of brain injury [32]. Santos et al [17] have also recently reported that three different PDE5 inhibitors are able to increase the levels of cGMP in SVZ cells and stimulate cell proliferation through the ERK/MAPK pathway in adult mice. However, to our knowledge, the effect of iNO on the developing SVZ was never investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also reported the proneurogenic effect of sildenafil on SVZ-derived cell culture [33] and in animal models of brain injury [32]. Santos et al [17] have also recently reported that three different PDE5 inhibitors are able to increase the levels of cGMP in SVZ cells and stimulate cell proliferation through the ERK/MAPK pathway in adult mice. However, to our knowledge, the effect of iNO on the developing SVZ was never investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that modulating the cell fate of endogenous NPCs in the developing brain could be an interesting strategy to promote repair. In addition, increasing evidence supports the relationship between the level of guanosine 3′,5′ cyclic monophosphate (cGMP), the main effector of NO biological effects, and the ability of the SVZ to produce NPCs [17]. Here, we ask the question whether iNO could promote the proliferation of NPCs within the SVZ in the uninjured developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…Indenopyrazole 21, a compound containing the indenopyrazole framework, was found to strongly inhibit HIF-1α transcriptional activity without affecting HIF-1α protein accumulation and HIF-1 heterodimerization 65. YC-1, an antiplatelet aggregation agent, was shown to dissociate the binding of HIFα T-CAD to p300 co-activator, leading to the repression of HIF transcriptional activity; YC-1 could also impair HIFα protein accumulation 2666. FM19G11, a novel chemical entity, significantly repressed p300, a histone acetyltransferase required as a co-factor for HIF-transcription activation, by inhibiting histone acetylation 5567…”
Section: Hif Inhibitors For Cancer Therapymentioning
confidence: 99%
“…Wang et al [11] were able to show that sildenafil increased phosphorylated Akt, which was associated with increases in phosphorylated GSK-3 and induction of neurogenesis in adult neural progenitor cells suggesting an important role of GSK-3 in neurogenesis. These effects of sildenafil on phosphorylated Akt are specific, as sildenafil did not change expression of phosphorylated ERK1/2 [11,12] . In addition, GSK-3 is also an important component of Wnt/β-catenin pathway signaling, which regulates neurogenesis during development [13,14] .…”
Section: Introductionmentioning
confidence: 99%